2016
DOI: 10.1371/journal.pone.0151486
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Lactoferrin against Chromium-Induced Acute Kidney Injury in Rats: Involvement of IL-18 and IGF-1 Inhibition

Abstract: Hexavalent chromium (CrVI) is a heavy metal widely used in more than 50 industries. Nephrotoxicity is a major adverse effect of chromium poisoning. The present study investigated the potential renoprotective effect of lactoferrin (Lf) against potassium dichromate (PDC)-induced acute kidney injury (AKI) in rats. Beside, because previous studies suggest that interlukin-18 (IL-18) and insulin-like growth factor-1 (IGF-1) play important roles in promoting kidney damage, the present work aimed to evaluate the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 76 publications
(82 reference statements)
12
44
0
3
Order By: Relevance
“…These findings also showed that the effect of the highest dose of inPDC was more destructive than that brought either by the other doses of inPDC or by ipPDC. The induction of oxidative stress by CrVI has been shown in many studies [46, 30]. Moreover, Wang et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings also showed that the effect of the highest dose of inPDC was more destructive than that brought either by the other doses of inPDC or by ipPDC. The induction of oxidative stress by CrVI has been shown in many studies [46, 30]. Moreover, Wang et al .…”
Section: Discussionmentioning
confidence: 98%
“…It can generate reactive oxygen species (ROS) during their reduction, and these ROS can cause injury to the cellular proteins, lipids, and DNA [4, 5]. Involvement of inflammation in the Cr-toxicity has been also reported [6]. The propagation of this inflammatory response is dependent upon the stimulation of signaling pathways within the cell that include many components work sequentially to control the reaction and to express cytokines [7].…”
Section: Introductionmentioning
confidence: 99%
“…Важкі метали є одним із найбільш розповсюджених хімічних факторів професійного ризику в умовах сучасної промисловості [1]. Сполуки шестивалентного хрому використовують на підприємствах кольорової металургії, хімічної та лакофарбової промисловості, текстильних і шкіряних заводах [2,3]. Біхромати використовують для виробництва сірників, сухих батарей, неорганічних пігментів, лакофарбових покриттів.…”
Section: Buchko_oksana@ukrnetunclassified
“…У складній системі біохімічної адаптації організму до токсичних впливів важких металів важливе значення має застосування антиоксидантів, як засобів, що гальмують утворення вільних радикалів та продуктів перекисного окиснення клітинних компонентів, тим самим забезпечуючи високий рівень обміну речовин та енергії [3,5]. До таких речовин належать сполуки гумінової природи, які проявляють імуномодулюючий, адаптогенний, антистресовий, гепатопротекторний і ензимостимулюючий ефект на живі системи.…”
Section: Buchko_oksana@ukrnetunclassified
See 1 more Smart Citation